2023
DOI: 10.1002/anie.202306501
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Catalytic Difluorocarbene Transfer via Palladium Catalysis

Abstract: A palladium‐catalyzed reductive difluorocarbene transfer reaction that tames difluorocarbene to couple with two electrophiles has been developed, representing a new mode of difluorocarbene transfer reaction. The approach uses low‐cost and bulk industrial chemical chlorodifluoromethane (ClCF2H) as the difluorocarbene precursor. It produces a variety of difluoromethylated (hetero)arenes from widely available aryl halides/triflates and proton sources, featuring high functional group tolerance and synthetic conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
(104 reference statements)
0
14
0
Order By: Relevance
“…On the basis of the known research and our previous work, we proposed a plausible mechanism (Scheme e). First, the oxidative addition of aryl halides 1 leads to the formation of aryl palladium species A .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…On the basis of the known research and our previous work, we proposed a plausible mechanism (Scheme e). First, the oxidative addition of aryl halides 1 leads to the formation of aryl palladium species A .…”
Section: Resultsmentioning
confidence: 93%
“…Difluorocarbene as a building block has been widely employed in organic synthesis, drug development, and medicinal chemistry, by leading to difluoromethyl ethers, gem -difluorocyclopropanes, and gem -difluoroalkenes from corresponding substrates. Owing to the inherent electrophilicity, difluorocarbene is apt to be captured by a nucleophile to render an anion intermediate in situ, which promptly reacts with an electrophile to enable the production of the difluoroalkylated compounds, however, the palladium-catalyzed coupling reaction of difluorocarbene has only been explored in recent years. In 2016, Zhang’s group reported the first example of a metal difluorocarbene-involved catalytic coupling reaction . Later on, the same group developed the research of palladium-catalyzed difluorocarbene transfer reaction, which could effectively couple difluorocarbene with proton sources and nucleophilic reagents, including aryl borons and terminal alkynes, and they synthesized, isolated, and characterized the first example of [Pd 0 ]CF 2, which shows strong nucleophilicity and can react with water to produce Pd II –CF 2 H. While [Pd II ]CF 2 exhibits electrophilicity and can be hydrolyzed by water to generate CO (Scheme a right).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 e ,8 The coordination model offers new opportunities for difluorocarbene chemistry, 9 and has found applications in the synthesis of unique R-CF 2 -R′ molecules (Scheme 1a, left side). 8 b ,10 In all of the above reactions, difluorocarbene functions as a CF 2 source without the loss of any fluorine atom. Recent studies have shown that difluorocarbene can also act as a nonfluorinated C 1 precursor of various functional groups, such as carbonyl, 8 b ,11 cyanide 12 and isocyanide 13 groups (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, it could be successfully captured when various heteroatomic nucleophiles and activated C–H nucleophiles were used, providing CF 2 -containing products . Moreover, a number of transformations with metal difluorocarbene ([M]=CF 2 ) have been published since the pioneering work of Zhang and co-workers in 2015, namely, the metal difluorocarbene involved catalytic coupling (MeDIC) reaction . Despite significant progress, cyclization with difluorocarbene remains a significant challenge due to the limited reaction types .…”
mentioning
confidence: 99%